A ZEB1/p53 signaling axis in stromal fibroblasts promotes mammary epithelial tumours - Fu, Rong; Han, Chen-Feng; Ni, Ting; Di, Lei; Liu, Li-Juan; Lv, Wen-Cong; Bi, Yan-Ran; Jiang, Nan; He, Yin; Li, Hong-Mei; Wang, Shui; Xie, Hui; et al. (Nature communications, 2019)
Accumulating evidence indicates that the zinc-finger transcription factor ZEB1 is predominantly expressed in the stroma of several tumours. However, the role of stromal ZEB1 in tumour progression remains unexplored. In this study, while interrogating human databases, we uncover a remarkable decrease in relapse-free survival of breast cancer patients expressing high ZEB1 levels in the stroma. Using a mouse model of breast cancer, we show that ZEB1 inactivation in stromal fibroblasts suppresses tumour initiation, progression and metastasis. We associate this with reduced extracellular matrix remodeling, immune cell infiltration and decreased angiogenesis. ZEB1 deletion in stromal fibroblasts increases acetylation, expression and recruitment of p53 to FGF2/7 , VEGF and IL6 promoters, thereby reducing their production and secretion into the surrounding stroma. Importantly, p53 ablation in ZEB1 stroma-deleted mammary tumours sufficiently recovers the impaired cancer growth and progression. Our findings identify the ZEB1/p53 axis as a stroma-specific signaling pathway that promotes mammary epithelial tumours. In epithelial cells Zeb1 is involved in the epithelial to mesenchymal transition. In this study, the authors show in a mouse model of breast cancer, that Zeb1 expression in stromal cells is required for tumour formation and metastasis.